Efetividade de um manual de exercícios domiciliares na promoção da continência urinária durante a gestação: Um ensaio clínico aleatorizado pragmático - de Assis, Liamara Cavalcante [UNESP]; Bernardes, João Marcos [UNESP]; Barbosa, Angélica Mércia Pascon [UNESP]; Santini, Ana Carolina Monteiro [UNESP]; Vianna, Luana Schneider [UNESP]; Dias, Adriano [UNESP] (FapUNIFESP (SciELO), 2015)
Purpose: To evaluate the effectiveness of an illustrated home exercise guide targeting the pelvic floor muscles in promoting urinary continence during pregnancy. Methods: A randomized clinical trial was performed with 87 participants, evaluated six times during pregnancy and divided into three groups: Gsup, supervised; Gobs, not supervised, and Gref, women who did not perform the home exercises program. A miction diary and perineometry were used to evaluate urinary incontinence (primary outcome) and pelvic floor muscle strength (secondary outcome), respectively. The Kruskal-Wallis test with post hoc Dunn's and chi-square and Z tests with Bonferroni correction were used for continuous variables and proportions, respectively, with the level of significance set at 5%. Results: At the end of the study, 6.9% of pregnant women in the Gsup and Gobs had urinary incontinence, while 96.6% of Gref women were incontinent. Regarding pelvic floor muscle function, Gsup and Gobs had mean contractions of 10 and 8.9 cmH2O, respectively, while Gref had a value of 4.7 cmH2O. Both results were significant. Conclusion: An illustrated home exercise guide targeting the pelvic floor muscles is effective in promoting urinary continence during pregnancy, even without permanent supervision.
Effectiveness of an illustrated home exercise guide on promoting urinary continence during pregnancy: A pragmatic randomized clinical trial
Keywords: Clinical trial; Exercise therapy; Pelvic floor; Pregnancy; Urinary incontinence; Women’s health